2006
DOI: 10.1007/s10669-006-7830-0
|View full text |Cite
|
Sign up to set email alerts
|

Potential environmental fate of elsinochrome A, a perylenequinone toxin produced in culture by bindweed biocontrol fungus Stagonospora convolvuli LA39

Abstract: The photosensitizing perylenequinone toxin elsinochrome A (EA) is produced in culture by the bindweed biocontrol fungus Stagonospora convolvuli LA39 where it apparently plays a pathogenicity related role. We investigated the fate of EA with reference to its stability under different temperature and light conditions. EA remained stable when boiled in water at 100°C for 2 h. Similarly, exposing EA to 3-27°C in the dark for up to 16 weeks did not affect its stability either in dry or in aqueous form. However, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…We therefore conclude that this strain will not result in populations dense enough to have negative effects on the environment and other organisms in the longer term. These findings significantly add to earlier studies of our research group corroborating the potential of S. convolvuli LA39 as an efficient and risk‐free biocontrol agent (Ahonsi et al. 2006; Boss et al.…”
Section: Discussionsupporting
confidence: 87%
“…We therefore conclude that this strain will not result in populations dense enough to have negative effects on the environment and other organisms in the longer term. These findings significantly add to earlier studies of our research group corroborating the potential of S. convolvuli LA39 as an efficient and risk‐free biocontrol agent (Ahonsi et al. 2006; Boss et al.…”
Section: Discussionsupporting
confidence: 87%
“…This concentration is 125 times lower than the LOEC for the most sensitive organism (Trichoderma atroviride, 5 ng mL À1 ), and thus far too low to be of any risk for the consumer. When estimating the risk of residues in agricultural products it must also be taken into account that normally the last mycoherbicide treatment is applied several weeks before harvest and that ELA is rapidly degraded by sunlight, as was demonstrated by Ahonsi et al (2006). They observed that ELA applied to an inert surface was degraded rapidly with a half-life of 14-99 h depending on the actual weather conditions.…”
Section: Stagonospora Convolvuli La39 Produces Metabolites With Toxicmentioning
confidence: 99%
“…The concentration of elsinochromes was determined by reference to a regression line that was established using pure cercosporin (Sigma, St Louis, MO, USA) as a standard, because no pure elsinochromes are commercially available. Cercosporin and elsinochromes have similar structures, molecular weights and absorbance spectra (Weiss et al., 1987; Ahonsi et al., 2006). Quantitative analysis of the elsinochromes was performed by extracting agar plugs containing fungal hyphae with 5 m KOH and by measuring absorbance at 480 nm.…”
Section: Methodsmentioning
confidence: 99%